The development of the creativity of the future teacher as a precondition for effective activity (Actual Problems of Psychology in Educational Institutions, 2022)
The article in question substantiates the necessity of developing of the creativity of future workers in education as a precondition for effective self-improvement and competence development. The results of the diagnostics of the criteria of creativity (speed, flexibility, originality, elaboration) are also presented. The level of the future professional activity’ development (prescriptive, algorithmic, copy) defined.The necessity of the implementation of innovative forms of education is grounded.
Keywords: creative thinking; creativity; levels of development; innovative forms of education